2008
DOI: 10.1038/onc.2008.138
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of E2F3a causes DNA damage leading to ATM-dependent apoptosis

Abstract: Many early stage human tumors display markers of a DNA-damage response (DDR), including ataxia telangiectasia mutated (ATM) kinase activation. This suggests that DNA damage accumulates during the process of carcinogenesis and that the ATM-dependent response to this damage may function to suppress cancer progression. The E2F3a transcription factor plays an important role in regulating cell proliferation and is amplified in a subset of human cancers. Similar to human premalignant lesions, we find activated ATM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…It has been suggested that oncogenes cause DNA damage by increasing the production of reactive oxygen species, by telomere attrition, or through the vague concept of replicative stress. Our finding that aphidicolin can block the activation of DDR in E2F1/E2F2 À/À cells has some similarity to other reports implicating aberrant DNA replication in oncogene-induced DNA damage (Bartkova et al, 2006;Di Micco et al, 2006;Paulson et al, 2008). It is possible that overexpression of the replication proteins Mcm2, Mcm3 and Cdc6 in E2F1/E2F2 À/À cells shown in this study may cause DNA damage by promoting illegitimate replication origin firing, which could, in turn, result in head-to-tail fork collision and checkpoint activation, similarly to what has been shown in cell extracts overexpressing the replication protein Cdt1 (Davidson et al, 2006).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…It has been suggested that oncogenes cause DNA damage by increasing the production of reactive oxygen species, by telomere attrition, or through the vague concept of replicative stress. Our finding that aphidicolin can block the activation of DDR in E2F1/E2F2 À/À cells has some similarity to other reports implicating aberrant DNA replication in oncogene-induced DNA damage (Bartkova et al, 2006;Di Micco et al, 2006;Paulson et al, 2008). It is possible that overexpression of the replication proteins Mcm2, Mcm3 and Cdc6 in E2F1/E2F2 À/À cells shown in this study may cause DNA damage by promoting illegitimate replication origin firing, which could, in turn, result in head-to-tail fork collision and checkpoint activation, similarly to what has been shown in cell extracts overexpressing the replication protein Cdt1 (Davidson et al, 2006).…”
supporting
confidence: 88%
“…Very rarely, a pre-cancerous cell with aberrant DNA replication could evade this tumor suppressive barrier, such as by mutating p53 (Di Micco et al, 2006). Activation of the DDR is common in cells and tissues that overexpress oncogenic regulators of cellular proliferation, such as Ras, Braf, mos, cyclin E or E2F3 (Bartkova et al, 2006;Di Micco et al, 2006;Paulson et al, 2008). It has been suggested that oncogenes cause DNA damage by increasing the production of reactive oxygen species, by telomere attrition, or through the vague concept of replicative stress.…”
mentioning
confidence: 99%
“…The pathways that were specifically enriched in adenomas in our analysis are known to be activated in colorectal carcinogenesis (causal, resulting or compensatory) such as the Wnt pathway (Midgley and Kerr, 1999), cell cycle routes (Hao et al, 1998), DNA base metabolism, transcription, ATM (Kwong et al, 2008;Paulson et al, 2008), ARF, p27 (Payne et al, 2008) and p53 (Einspahr et al, 2006) signaling routes. In addition, we found novel pathways unique to adenomas, among which are the Rb pathway, the Src pathway, folate biosynthesis and the PTC1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Given that we obtained evidence that JCV-infected oligodendrocytes were arrested at the G 2 phase in a brain of an individual with PML, ATM-ATR inhibitors such as caffeine might prove clinically effective against JCV infection. Although it is difficult to assess the antiviral effect of caffeine at a nontoxic dose in vivo because of the lack of an animal model of JCV infection, recent studies have shown that the administration of caffeine in drinking water resulted in the inhibition of ATM or ATR signaling pathways in mice (49,50). In addition, given that it readily crosses the blood-brain barrier, caffeine is likely to have access to target cells in central nervous system diseases such as PML.…”
Section: Discussionmentioning
confidence: 99%